2014
DOI: 10.1016/s2095-3119(13)60665-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Source-Sink Manipulation on Photosynthetic Characteristics of Flag Leaf and the Remobilization of Dry Mass and Nitrogen in Vegetative Organs of Wheat

Abstract: The photosynthetic characteristics of flag leaf and the accumulation and remobilization of pre-anthesis dry mass (DM) and nitrogen (N) in vegetable organs in nine wheat cultivars under different source-sink manipulation treatments including defoliation (DF), spike shading (SS) and half spikelets removal (SR) were investigated. Results showed that the SS treatment increased the photosynthetic rate (Pn) of flag leaf in source limited cultivar, but had no significant effect on sink limited cultivar. The SR treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 25 publications
1
13
0
2
Order By: Relevance
“…The present results are consistent with those of Voltas et al (1997) which also showed a larger increase in grain weight increment following sink reduction for smaller TGW genotypes (14.6% to 25.1% grain weight increase) for three barley genotypes; but the spikelet removal treatment was applied early at anthesis and might have altered the sink potential size (Dupont & Altenbach, 2003;Calderini et al, 2001;Cartelle et al, 2006). Furthermore, Zhang et al (2014) 350 found that eight out of the nine wheat genotypes in a field experiment in China showed a similar negative relation between control grain weight and TGW increase following spikelet removal, although low TGW increases were observed (< 12%). Similarly, Serrago et al (2011) using three contrasted cultivars found the TGW increase following fungicide treatment was highly correlated to healthy area absorption per grain (HAA G ), a unique relationship being observed when HAA G was related to TGW of healthy crops.…”
supporting
confidence: 90%
See 2 more Smart Citations
“…The present results are consistent with those of Voltas et al (1997) which also showed a larger increase in grain weight increment following sink reduction for smaller TGW genotypes (14.6% to 25.1% grain weight increase) for three barley genotypes; but the spikelet removal treatment was applied early at anthesis and might have altered the sink potential size (Dupont & Altenbach, 2003;Calderini et al, 2001;Cartelle et al, 2006). Furthermore, Zhang et al (2014) 350 found that eight out of the nine wheat genotypes in a field experiment in China showed a similar negative relation between control grain weight and TGW increase following spikelet removal, although low TGW increases were observed (< 12%). Similarly, Serrago et al (2011) using three contrasted cultivars found the TGW increase following fungicide treatment was highly correlated to healthy area absorption per grain (HAA G ), a unique relationship being observed when HAA G was related to TGW of healthy crops.…”
supporting
confidence: 90%
“…Although not validated yet, tolerance could rely on post-anthesis RUE increase in response to lower assimilate availability relative to sink strength. More recently, Zhang et al (2014) suggested a positive feedback from the sink strength on sources: an altered source/sink balance, decreased by ear shading or increased by spikelet removal treatments in wheat, led to either up-regulation or down-regulation of flag-leaf photosynthetic 60 rate.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Це пов'язано переважно з високим вмістом азоту в листках у фазу цвітіння. Отримані результати добре узгоджуються з літературними даними щодо вирішального внеску листків у забезпечення зерна пшениці азотом [28]. Разом з тим за високого рівня мінерального живлення різниця між сортами за К р для листків була не такою значною, як для цілого пагона.…”
Section: результати та обговоренняunclassified
“…through ear (awn) removal/shading or application of herbicides [15,25,28], isotope tracing [19], gas exchange measurement of excised spikelets [6,8] and chlorophyll fluorescence measurement for plants cultured in pots [26]. Among these methods, the shading treatments or applications of herbicides may affect function of organs or trigger compensation effects of unaffected organs [18,20,[29][30][31][32][33]. The stable isotope discrimination method compared instant carbon isotope in water-soluble fraction in different tissues at mid-grain filling stage and carbon isotope in mature grains, the accuracy of which might be affected by the dynamic environment (e.g.…”
Section: Introductionmentioning
confidence: 99%